2002
DOI: 10.1093/carcin/23.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein 2A expression is associated with cell proliferation in breast cancer

Abstract: Metallothioneins (MTs) belong to a family of cysteine-rich, metal-binding intracellular proteins, which have been linked with cell proliferation. In this study, expression levels of the 8 known MT-1 and MT-2 functional isoforms in human invasive ductal breast cancer specimens were determined by RT-PCR. The expression profiles of the MT protein and MT-2A mRNA were further evaluated in 79 cases of human invasive ductal breast carcinoma by immunohistochemistry and in situ hybridization, and correlated with cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
122
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(137 citation statements)
references
References 39 publications
14
122
1
Order By: Relevance
“…MT2A mRNA transcript has been reported to positively correlate with cell proliferation and histological grading of breast cancer (Jin et al, 2002). In urological malignancies, up-regulation of MT2A and down-regulation of MT1A and MT1G mRNA levels have been detected in renal cancer tissues (Nguyen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…MT2A mRNA transcript has been reported to positively correlate with cell proliferation and histological grading of breast cancer (Jin et al, 2002). In urological malignancies, up-regulation of MT2A and down-regulation of MT1A and MT1G mRNA levels have been detected in renal cancer tissues (Nguyen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…MTs are a group of intracellular low molecular (6 -7 kDa), cysteine-rich, metal-binding proteins, acting as scavengers of toxic metal ions or reactive oxygen species. MTs have been implicated in the regulation of cell proliferation and apoptosis (11,12), suggesting a role for MTs in cell survival. MT function in heavy metal detoxification primarily depends on the high affinity binding between the heavy metals and MTs, leading to the sequestration of metals away from critical macromolecules (13,14).…”
Section: Induction Of Metallothionein (Mt) Expression Is Involved In mentioning
confidence: 99%
“…An increase in MT expression in tumor cells correlates with expression of Ki-67 proliferation antigen and a less favorable outcome of the disease [6, 7, 14--16]. It has been shown that MT-2A isoform expression in breast cancer cells stimulates cell proliferation, but does not exert anti-apoptotic properties [17]. Moreover, a decline of MT-I/II expression is associated with a decrease of PCNA and Ki-67 expression both in sun-exposed and sun-protected skin, which may indicate its impact on cell proliferation [18].…”
Section: Introductionmentioning
confidence: 99%